Microarray-based understanding of normal and malignant plasma cells - De Vos, John; Hose, Dirk; Rème, Thierry; Tarte, Karin; Moreaux, Jérôme; Mahtouk, Karéne; Jourdan, Michel; Goldschmidt, Hartmut; Rossi, Jean-François; Cremer, Friedrich Walter; Klein, Bernard (Immunological reviews, 2006)
Summary: Plasma cells (PCs) develop from B lymphocytes following stimulation by antigen and express a genetic program aimed at the synthesis of immunoglobulins. This program includes the induction of genes coding for transcription factors such as PRDM1, X-box-binding protein 1 and BHLHB3, cell-surface molecules such as CD138/syndecan-1, and for the unfolded protein response. We review how the microarray technology has recently contributed to the understanding of the biology of this rare but essential cell population and its transformation into premalignant and malignant PCs.